(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the importance of cultural literacy in the education of elementary school children. The research method used is the literature review method, which focuses on analyzing the latest relevant literature. Articles are obtained from various valid sources, namely google scholar. The results show that the importance of implementing cultural literacy education in primary schools is a complex challenge, but it can be overcome through a holistic approach and planned solutions. The key to success in bringing this concept into the classroom involves teacher training, integration of cultural literacy materials in the curriculum, and parent and community participation. Close collaboration between various parties, including the government and higher education institutions, as well as adjustments to supportive education policies, are important steps to create a learning environment that can provide children with a deep understanding of cultural diversity